Studies 0n Ion Association of Some Α-Amino Acids with L-Ascorbic Acid In Aqueous Solution at Different Temperature - Kadhim, Mohammed J. (Iraqi Journal of Science, 2019)
Molar conductivity of ascorbic acid (AA) with some α–amino acids (glycine (Gly), methionine (Met), cysteine (Cys) and tryptophan (Trp)) in aqueous solution was measured at range temperatures from 298 K to 313 K. Λo. The limiting molar conductivity, KA, the association constant was calculated using the Shedlovsky method, and R, the association distance calculated by Stokes–Einstein equation. The thermodynamic parameters (The heat of association ΔHo, the change in Gibbs free energy ΔGo, the change of entropy ΔSo), and (ΔES), the activation energy were also calculated. All of the results obtained were discussed. The data showed the increasing in Λo, with the increasing of temperature. The positive values for (ΔSo) and (ΔES) showed a decrease in solvation of ion–pair and signifying the higher mobility of the ions. The negative value of ΔHo, refers that the association processes are exothermic. The negative values of ΔGo, are for ion association in aqueous solution and increase with the increase in temperature.